2010
DOI: 10.1007/s11738-010-0506-x
|View full text |Cite
|
Sign up to set email alerts
|

The use of network analysis to uncover homeostatic responses of a drought-tolerant sugarcane cultivar under severe water deficit and phosphorus supply

Abstract: The objective of this study was to identify how changes in the photosynthetic network would be linked to the homeostasis modulation of a drought tolerant sugarcane cultivar subjected to severe water deficit. Moreover, we tested the potential effect of phosphorus supply on the plant physiological responses to drought, because such element is essential to photosynthetic processes. This study was carried out in a greenhouse, where sugarcane plants (Saccharum spp.) cv. RB 86-7515 were grown. One singlenode stalk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 31 publications
3
19
1
1
Order By: Relevance
“…In our study, the curling of dwarf bamboo leaves was observed when water stress decreased the LRWC. Several studies have shown that P fertilization can directly enhance LRWC, as well as free and bound water components in water-stressed plants (Singh et al, 2006a;Sato et al, 2010). However, P application had minimal effect on LRWC of dwarf bamboo, regardless of water availability (Table 2), as also shown in previous studies of other crop species Singh et al, 2006b;Burman et al, 2009).…”
Section: Growth and Water Statussupporting
confidence: 63%
See 2 more Smart Citations
“…In our study, the curling of dwarf bamboo leaves was observed when water stress decreased the LRWC. Several studies have shown that P fertilization can directly enhance LRWC, as well as free and bound water components in water-stressed plants (Singh et al, 2006a;Sato et al, 2010). However, P application had minimal effect on LRWC of dwarf bamboo, regardless of water availability (Table 2), as also shown in previous studies of other crop species Singh et al, 2006b;Burman et al, 2009).…”
Section: Growth and Water Statussupporting
confidence: 63%
“…Statistics as in 2.72 ± 0.08 b 2.63 ± 0.06 b 3.00 ± 0.10 a 2.70 ± 0.04 a* Proline (mg g À1 DW) 0.41 ± 0.13 b 0.40 ± 0.10 b 1.88 ± 0.17 a 1.28 ± 0.10 a* confirmed in several plants (dos Santos et al, 2004;Garg et al, 2004;Burman et al, 2009;Sato et al, 2010). Meanwhile, some other reasons may have contributed to the improvement of P n after P application, including increased ATP and NADPH productions, activated enzyme activities in Calvin cycle, enhanced regeneration of sugar phosphate, higher output rate of photosynthates and cell proliferation (Rao and Terry, 1995).…”
Section: Tablementioning
confidence: 77%
See 1 more Smart Citation
“…& G. M. Souza gumaia.gms@gmail.com deficit is associated with a decrease in leaf gas exchange (Inman-Bamber and Smith 2005;Smit and Singels 2006;Sato et al 2010). Initially, stomatal conductance decreases; however, the internal CO 2 concentration remains unchanged due to CO 2 concentrating mechanisms of C4 plants (Saliendra et al 1996;Ripley et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Elgharably [23] found that 60 mg kg −1 P significantly increased wheat biomass and P accumulation under salt stress by reducing the Cl − and Na + uptake in the root and increasing root biomass. P fertilizer promoted sucrose accumulation in the plant by effectively improving cellular water status and photosynthetic stability [47]. P can promote water and nutritional uptake by accelerating root growth, increasing the root/shoot ratio, secreting organic acids and other mechanisms [48,49].…”
Section: Dw and P Accumulationmentioning
confidence: 99%